Technology Entrepreneurship Project (ENT 600) : Smart Motorcycle Helmet / Ahmad Ridhwan Ahmad Nasaruddin - Ahmad Nasaruddin, Ahmad Ridhwan; Zaini, Mohamad Aiman; Hamedin, Muhammad Arif Aiman; UMAR, Muhammad Helmi Fariz; Ismail, Mohamd Ilman (2021)
This report is from the Technology Entrepreneurship subject which serves to innovate a product and incorporate technological elements into the product. In the introduction, we have talked about the products that will be done in the success of this innovative report to run products related to helmets and give additions to those products to be marketed. In addition, there are statements of problems, objectives and methodologies, each providing a description of how this product is done. Next, in the new product development section, there is a more detailed product enlightenment that will be explained in this section, namely product definition, classification, and process to NPD which is divided into five parts, namely research and development, product design and features, concept testing, prototype, and test marketing. The happy part tells about this product in more depth because in this section can be clearly seen the description of the product that this delivered. In the next section is a conclusion that tells the whole about what is found in this report, followed by references and appendices that provide material for the reader to refer to and the evidence of this report is produced.